2018
DOI: 10.1038/s41437-018-0093-y
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational effects of maternal sexual interactions in seed beetles

Abstract: Mating often bears large costs to females, especially in species with high levels of sexual conflict over mating rates. Given the direct costs to females associated with multiple mating, which include reductions in lifespan and lifetime reproductive success, past research focused on identifying potential indirect benefits (through increases in offspring fitness) that females may accrue. Far less attention has, however, been devoted to understanding how costs of sexual interactions to females may extend across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…direct or female‐moderated paternal effects arising from variation in the non‐sperm fraction of the ejaculate (Garcia‐Gonzalez & Simmons, 2007; Gasparini et al ., 2018)]. However, any inter‐generational or trans‐generational effect has the capacity to significantly alter the economics of sexual interactions (Dowling, Williams, & Garcia‐Gonzalez, 2014; Zajitschek et al ., 2018), leading to unknown but presumably significant effects on sexual selection. We anticipate that investigations focusing on how temperature‐driven maternal and paternal effects impact sexual selection will yield important insights.…”
Section: Processes Involved In Effects Of Temperature On Sexual Selecmentioning
confidence: 99%
“…direct or female‐moderated paternal effects arising from variation in the non‐sperm fraction of the ejaculate (Garcia‐Gonzalez & Simmons, 2007; Gasparini et al ., 2018)]. However, any inter‐generational or trans‐generational effect has the capacity to significantly alter the economics of sexual interactions (Dowling, Williams, & Garcia‐Gonzalez, 2014; Zajitschek et al ., 2018), leading to unknown but presumably significant effects on sexual selection. We anticipate that investigations focusing on how temperature‐driven maternal and paternal effects impact sexual selection will yield important insights.…”
Section: Processes Involved In Effects Of Temperature On Sexual Selecmentioning
confidence: 99%
“…In general, experimental studies show that females continuously housed with males have lower fitness than females that only have intermittent access to males (Edvardsson, ; Lew, Morrow, & Rice, ; Rönn et al , ). In most of these studies, however, researchers cannot determine the relative effects of the actual rate of copulation from those of male sexual harassment: the increased presence of males leads to both greater male harassment and a higher mating rate (but see Fox, Head, & Jennions, ; den Hollander & Gwynne, ; Partridge & Fowler, ; Zajitschek, Dowling, Head, Rodriguez‐Exposito, & Garcia‐Gonzalez, ). The distinction between these two processes matters.…”
Section: Introductionmentioning
confidence: 99%
“…For example, females might allocate fewer resources to eggs or decrease parental care to ameliorate costs of repeated copulation or greater male harassment. To date, the effects of increased male presence on offspring fitness have rarely been quantified (Brommer, Fricke, Edward, & Chapman, 2012;Le Galliard, Cote, & Fitze, 2008;Priest, Galloway, & Roach, 2008;Zajitschek et al, 2018) and studies have found conflicting results, even within a species. For example, Dowling, Williams, and Garcia-Gonzalez (2014) showed that female Drosophila melanogaster experiencing more sexual interactions produced offspring with lower survival and higher rates of senescence, whereas Priest et al (2008) found that females that mated more often produced daughters with greater lifetime reproductive success.…”
Section: Introductionmentioning
confidence: 99%
“…In those studies that come closest, the level of male harassment is varied while controlling for the cost of mating (i.e. female only mated once), but the individual effects of polyandry and male harassment are conflated in treatments where increased harassment and increased number of mates is associated with an increased mating rate (den Hollander and Gwynne 2009;Zajitschek et al 2018). More studies that use our design to simultaneously examine the effects of male harassment and polyandry, while controlling for the actual mating rate are needed to quantify how costly male sexual harassment really is for females.…”
Section: The Importance Of Disentangling Male Harassment From Polyandrymentioning
confidence: 99%
“…To our knowledge, only one study has simultaneously examined the costs/benefits of male sexual harassment and polyandry (i.e. number of males inseminating) while controlling for the mating rate (Zajitschek et al 2018).…”
Section: Introductionmentioning
confidence: 99%